2019
DOI: 10.3390/ijms21010047
|View full text |Cite
|
Sign up to set email alerts
|

Human Molecular Chaperone Hsp60 and Its Apical Domain Suppress Amyloid Fibril Formation of α-Synuclein

Abstract: Heat shock proteins play roles in assisting other proteins to fold correctly and in preventing the aggregation and accumulation of proteins in misfolded conformations. However, the process of aging significantly degrades this ability to maintain protein homeostasis. Consequently, proteins with incorrect conformations are prone to aggregate and accumulate in cells, and this aberrant aggregation of misfolded proteins may trigger various neurodegenerative diseases, such as Parkinson’s disease. Here, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…The cell viability measurements were performed according to previous studies on the mouse neuroblastoma cell line Neuro2a (N2a), using a Tali™ Image-Based Cytometer (Thermo Fisher Scientific, Waltham, MA, USA) [ 28 ]. N2a cells were obtained from Public Health England.…”
Section: Methodsmentioning
confidence: 99%
“…The cell viability measurements were performed according to previous studies on the mouse neuroblastoma cell line Neuro2a (N2a), using a Tali™ Image-Based Cytometer (Thermo Fisher Scientific, Waltham, MA, USA) [ 28 ]. N2a cells were obtained from Public Health England.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, it has been shown that, in vitro, HSP70 alone or in cooperation with different chaperones/co-chaperones inhibits formation of α-synuclein fibrils [ 35 , 36 ] and tau aggregates [ 32 ], and reduces polyglutamine (polyQ)-induced toxicity when exogenously added to cultured cells [ 37 ]. Other chaperones such as HSP60 and HSP40 have been shown to suppress α-synuclein fibrillization in vitro and to block the polyQ-induced toxicity, respectively [ 38 , 39 ]. In turn, overexpression of αB-crystallin and HSP27, members of small heat shock protein family (sHSP), significantly reduces the intracellular aggregation of α-synuclein and inhibits cytotoxicity of α-synuclein fibrils [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…pCAG-GFP and mCherry2-N1 genes were a gift from Connie Cepko (Addgene plasmid # 11150; http://n2t.net/addgene:11150 ; RRID:Addgene_11150) and from Michael Davidson (Addgene plasmid # 54517; http://n2t.net/addgene:54517 ; RRID:Addgene_54517), respectively. The plasmid pCAG-GFP-αSyn was previously constructed in our laboratory ( 59 ). pCAG-FABP3-mCherry was prepared by substituting the GFP ORF of pCAG-GFP with a synthetic FABP3-mCherry gene (Integrated DNA Technologies).…”
Section: Methodsmentioning
confidence: 99%